Effects of Different Pre-Treatments on Local Pineapple Leaf as a Potential Substrate for the Production of Value-Added Products - Alexander C., Dennis; Rosmawati, Saat (Academy of Sciences Malaysia, 2024)
Lignocellulosic biomass such as pineapple leaves can be applied as substrates in various biochemical processes such as solid-state fermentation to produce industrially important enzymes or other value-added products. However, recalcitrant nature of the biomass hinders the accessibility of cellulose for enzymatic hydrolysis in yielding high amounts of the intended products. In order to overcome this obstacle, pre-treatment is necessary as to loosen the lignocellulose structure to ease accessibility of enzymes and biodegradability of the biomass. In this study, local pineapple leaves were subjected to different methods of pre-treatments which are thermal pre-treatment by autoclaving, and chemical pre-treatments involving treatments with alkaline solutions (1% and 1.5% (w/v) sodium hydroxide) as well as acid solutions (1% and 1.5% (v/v) hydrochloric acid). Scanning Electron Microscopy was conducted to compare and study the effect of different pre-treatments on morphological changes of raw and pre-treated leaves. The obtained results revealed that the biomass was severely affected by 1.5% (v/v) hydrochloric acid solution as the surface structure was vigorously ruptured and more aggregated cracks were clearly visible in most parts, compared to the surface morphologies observed on raw samples and samples with other pre-treatment methods.